Barriers to physical activity among cancer pediatric cancer patients and survivors: a scoping review - Guimarães, Jean Augusto Coelho [UNESP]; Guerra, Paulo Henrique; Ueno, Deisy Terumi [UNESP]; Spósito, Letícia Aparecida Calderão [UNESP]; Sebastião, Emerson; Nakamura, Priscila Missaki [UNESP]; Fernandes, Romulo A. [UNESP] (FapUNIFESP (SciELO), 2022)
Aim: The present scoping review aims to provide an overview of barriers to PA reported by pediatric cancer patients undergoing treatment as well as after treatment. This study further aims to describe and discuss the instruments used for assessing barriers in this population. Methods: Article search was performed in common medical databases and yielded five original research articles. Results: The included articles reported barriers to PA that can be grouped into the following categories: individuals, physical, environmental, and treatment. Among the instruments used to assess barriers to PA, it was observed that questionnaires and interviews are commonly adopted. This review underscores a paucity of studies in this area. Conclusion: A comprehensive understanding of barriers to PA in the pediatric cancer population is paramount for the development of tailored strategies and interventions aiming to promote PA in this under-researched group. In addition, future studies must adopt a mixed-methods approach, longitudinal design with specific instruments in the pediatric cancer population.
Keywords: Barriers; Oncology; Pediatric; Physical activity